2011
DOI: 10.1128/jvi.02602-10
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Human Polyomavirus Closely Related to the African Green Monkey-Derived Lymphotropic Polyomavirus

Abstract: We identified a novel human polyomavirus from a kidney transplant patient under immunosuppressive treatment, by use of a generic PCR. The genome of the virus was completely amplified and sequenced. In phylogenetic analyses, it appeared as the closest relative to the African green monkey-derived lymphotropic polyomavirus (LPV). Further investigation of clinical samples from immunocompromised patients with specific nested PCR revealed additional positive samples, indicating that the virus naturally infects human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
216
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(225 citation statements)
references
References 17 publications
4
216
1
4
Order By: Relevance
“…1b) and respective splice sites ( Table 2). The STAg CDS had been predicted as unspliced [48] (Fig. 1a).…”
Section: Analysis Of Splicing In the Early Region Of Hpyv9 And Hpyv12mentioning
confidence: 99%
See 2 more Smart Citations
“…1b) and respective splice sites ( Table 2). The STAg CDS had been predicted as unspliced [48] (Fig. 1a).…”
Section: Analysis Of Splicing In the Early Region Of Hpyv9 And Hpyv12mentioning
confidence: 99%
“…We recently discovered two hitherto unknown human polyomaviruses, human polyomavirus 9 (HPyV9) in the serum of a kidney transplant recipient in 2011 [48], and human polyomavirus 12 (HPyV12) in metastatic liver tissue of patients with colorectal cancer [49]. Both viruses are circulating in the human population, as seroprevalences of 20-70 % against VP1 of HPyV9 have been readily detected in several studies, and for HPyV12 a VP1-based seroprevalence of 23 % was reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas HPyV6 and HPyV7 were first detected on skin of healthy subjects (23), HPyV9 was found is a serum sample of a kidney transplant patient (24). HPyV10 was identified in papillomavirus-induced anal condylomata (25) and the Malawi polyomavirus (MWPyV) and the MX polyomavirus (MXPyV), both identified in stool samples, are variants of HPyV10 (26,27).…”
mentioning
confidence: 99%
“…[159], [260] MCPyV DNA is detected in 75% of environmental swabs, and can still be detected after DNAse digestion, suggesting that like HPyV6,7 & 9, MCPyV is shed as whole virions from healthy human skin. [9], [167], [260] Therefore contamination of samples with MCPyV from the environment and healthy skin is likely, and detection of MCPyV DNA from different sites, particularly the skin is likely to be overestimated.…”
Section: Human Polyomaviruses and Cancermentioning
confidence: 99%